Vibration transmissibility suppression for hydraulic excavators in working conditions via multi-objective optimization. (January 2022) - Chen, Yong; Jiang, Mian; Wang, Daoyong; He, Kuanfang
The mass variances of materials in buckets and the movements of excavation arms greatly impact powertrain vibration transmissibility in hydraulic excavators under working conditions. If the influence of mass variation among bucket contents and excavation arm motions on vibration transmissibility is not considered, then only limited improvements can be made to vibration isolation performance. In this paper, vibration transmissibility suppression for hydraulic excavators operating under working conditions were studied via multi-objective optimization for stiffness coefficients of suspension elements (SEs). First, the rigid-flexible coupling model of a hydraulic excavator with a flexible base was built using ADAMS software. In the model, the stiffness coefficients of the SEs were the targeted variables with constrained conditions, while the multi-objectives for optimization were the vibration transmissibility and energy decoupling rates of the powertrain. Vibration isolation transmissibility (VIT) of the mounting system was compared between situations with non-optimized and optimized stiffness coefficients. Finally, the amplitude changes of the resultant SE support forces were used to illustrate the effects of powertrain vibration transmissibility suppression. We found that the average value of VITs increases significantly during the optimization process for the stiffness coefficients of SEs, which indicates that the mounting system has better vibration isolation performance. The smaller amplitudes of the resultant support force illustrate the improvements to the performance of vibration transmissibility suppression of the powertrain via the optimization process.